Citizen participation and education: new challenges in the digital age - González - Andrío Jiménez, Rocío; Palomero-Ilardia, Irene (Clio. History and History Teaching, 2021)
The main objective of this article is to explain the concept of citizen participation and the education on it. In our changing, global and digital society in which the democratization of knowledge is a reality, educational challenges are increasing. This article emphasizes the importance of includinga specific education to teach how to participate offline and online both in the subjects of Social Sciences in Primary School and Geography and History in Secondary School,
Keywords: citizen participation, civic education, digital citizenship, democracy, educational practices